UMAR BIN KHATTAB'S PERSPECTIVE EDUCATION MANAGEMENT - Amrin Sofian (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2022)
Abstract Educational management is an integral part of the overall educational process. The pattern of education at the time of Umar bin Khattab certainly had a tremendous impact in the current era. So this study examines the educational management perspective of Umar Bin Khattab. This research is literature research and the methodology used in this research is character study. The data related to this study were collected through literature study and presented with descriptive analysis techniques, namely by explaining the educational management of Umar bin Khattab during his leadership era, by referring to the book of Umar bin Khattab's sirah as primary data and literature books that related as secondary data. The results of this study are the management of education in Umar Bin Khattab's leadership of public services is the bookkeeping of the Qur'an, qira'at education, Tafsir bil Ra'yi education, education in the dissemination of hadith and infrastructure education (architect).